Relationship Between Sulcal Characteristics and Brain Aging - Jin, Kaide; Zhang, Tianqi; Shaw, Marnie; Sachdev, Perminder; Cherbuin, Nicolas (Frontiers in Aging Neuroscience, 2018)
This study aimed to determine whether sulcal morphology differs between middle age and older healthy individuals. Furthermore, we sought to determine whether age-related differences in sulcal characteristics were more strongly associated with differences in local or global cortical volumes. Participants (age 44-50, N=403; age 64-70, N=390) from the PATH Through Life study were included. Sulci were 17.3% wider, on average, in old age compared to middle age participants, with the largest difference in the left superior frontal sulcus. Differences in the width of the superior frontal and central sulci were significantly associated with differences in the volume of adjacent local gyri, while age-related differences in the width of lateral and superior temporal sulci were associated with differences in whole brain cortical volume. These findings suggest that sulcal characteristics provide unique information about changes in local and global brain structure in ageing.